Collecting Taxes - Harley, Geoff (Victoria University of Wellington Law Review, 2002)
This paper provides an account of the nature and development of tax law. The author argues that tax law touches human activities to the extent that it is an accurate predictor of human and corporate behaviour. The paper examines several prominent tax cases, including Sir Ivor Richardson’s involvement in the Duke of Westminster, Europa Oil and Re Securitibank decisions. In particular, the author discusses Sir Ivor’s "no halfway house" rule (which focuses on the true nature of any given transaction by a consideration of the legal character of the agreement which embodies the transaction). The importance of the "no halfway house" rule is discussed through several tax cases. Finally, the author argues that even rational judges tend to adopt a "pure gut" response to tax disputes. In light of all of the above, the author praises Sir Ivor’s impact on tax law, stating that his judgments would be sure to have an enduring benefit.